DIVERSITY AND ABUNDANCE OF BENTHIC INSECTS IN RELATION TO WATER POLLUTION IN A SEWAGE FED POND - HABEEBA AHMAD KABIR; SALTANAT PARVEEN; UZMA AHMAD (The Bioscan, 2012)
The aim of present work was to analyze the diversity and abundance of benthic macro insect assemblages and pollution level in a sewage fed pond. Samples were collected monthly over 1 year-cycles (February, 2009–January, 2010). This pond situated in Aligarh western region of U.P. is highly variable and sewage fed pond, has been used by fishermen. However, there is a concern about the impact of pollution on natural ecosystem, this study was conducted to evaluate insect occurrence and variation in terms of diversity and density in sewage fed water body so that one can know quality of water of other such ponds of this region. Benthic insect fauna was sampled with the help of Ekmann dredge. Five major groups (Diptera, Coleoptera, Hemiptera, Tricophtera and Ephemeroptera) and 19 species were identified. During summer season the density and abundance of insect fauna dropped inside sediment by around 49% indicating different responses during different months,. The value of Shannon diversity index ranged between 2.41-2.45. The fluctuation in the density as well as diversity indicated high pollution during winter season as compared to summer when pollution was low.